1995
DOI: 10.1002/humu.1380050302
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin mutations in health and disease

Abstract: To date, over 40 different mutations in transthyretin (TTR) have been associated with amyloid deposition. The major unresolved problem is the correlation between the clinical heterogeneity and the genetic heterogeneity. For instance, whereas some mutations produce neuropathy and some give rise to cardiomyopathy, others produce vitreous opacities, the vast majority being neuropathic. Moreover, some mutations are not amyloidogenic but are responsible to hyperthyroxinemias (by virtue of the protein function in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(28 citation statements)
references
References 42 publications
(10 reference statements)
0
28
0
Order By: Relevance
“…Transthyretin carries a substantial quantity of thyroxine (T 4 ) in the CSF, but in the blood, the two T 4 -binding sites of TTR are 99% unoccupied owing to the presence of additional T 4 carriers 280 . Substantial biophysical data suggest that in the case of the 125+ distinct mutations linked to the familial TTR amyloidoses 281 (http://amyloidosismutations.com/mut-attr.php), incorporation of mutant TTR subunits into a TTR tetramer otherwise composed of WT subunits destabilizes the heterotetramer—leading to faster TTR tetramer dissociation kinetics (kinetic destabilization), an increased population of misfolded aggregation-prone TTR monomer (thermodynamic destabilization), or both 282, 283 . Kinetic destabilization is especially relevant for aggregation and likely for disease progression, since TTR tetramer dissociation is the rate-limiting step in the amyloidogenesis cascade (see figure) 25, 26 .…”
Section: Figurementioning
confidence: 99%
“…Transthyretin carries a substantial quantity of thyroxine (T 4 ) in the CSF, but in the blood, the two T 4 -binding sites of TTR are 99% unoccupied owing to the presence of additional T 4 carriers 280 . Substantial biophysical data suggest that in the case of the 125+ distinct mutations linked to the familial TTR amyloidoses 281 (http://amyloidosismutations.com/mut-attr.php), incorporation of mutant TTR subunits into a TTR tetramer otherwise composed of WT subunits destabilizes the heterotetramer—leading to faster TTR tetramer dissociation kinetics (kinetic destabilization), an increased population of misfolded aggregation-prone TTR monomer (thermodynamic destabilization), or both 282, 283 . Kinetic destabilization is especially relevant for aggregation and likely for disease progression, since TTR tetramer dissociation is the rate-limiting step in the amyloidogenesis cascade (see figure) 25, 26 .…”
Section: Figurementioning
confidence: 99%
“…13 Extracelluar deposition of TTR aggregates in various organs including heart, lung, and peripheral nerves is associated with senile systemic amyloidosis, familial amyloidotic polyneuropathy, familial amyloid cardiomyopathy, and rarely central nervous system selective amyloidosis. 46 The TTR amyloidoses exhibit extreme variations of the disease phenotype. 4,79 For example, aggregation of wild-type (WT) TTR affects primarily the heart and lung, causing senile systemic amyloidosis that affects nearly 25% of the population over age 80.…”
Section: Introductionmentioning
confidence: 99%
“…The biosynthesis, the various structural domains, cleavage sites and a few selected key mutations in hTTR are shown schematically in Figure 1. The above single monomeric chain forms a strong tetrameric complex (Calculated MW ~55,044 Da) that exhibits its physiological and biological activity [33][34][35]. A recent study with hTTR wild type as well as its key physiological mutant variants suggested that each monomeric form of hTTR is proteolytically cleaved likely by a trypsin like enzyme and this site may be located not far from 50 amino acids from the N-terminal end.…”
Section: Peptide Designmentioning
confidence: 99%
“…Along with this wild type peptide we also designed two additional peptides which contain the physiologically relevant mutations Ser 52 /Pro and Thr 49 /Ala. The rationale for this is based on the published observation that implicated the first mutation (Ser 52 /Pro) to most pathogenic state of amyloidosis followed by the second mutation (Thr 49 /Ala) [33,35]. A fourth peptide containing Lys 48 / Ala mutation has also been designed in order to examine the importance of basic Lys 48 residue in hTTR proteolysis.…”
Section: Peptide Designmentioning
confidence: 99%
See 1 more Smart Citation